The Combination of Serious Gaming and Immersive Virtual Reality through the Constructivist Approach: An Application to Teaching Architecture - Irene Capecchi; Tommaso Borghini; Elena Barbierato; Andrea Guazzini; Elena Serritella; Tommaso Raimondi; Claudio Saragosa; Iacopo Bernetti (MDPI AG, 2022)
Immersive virtual reality (IVR) has proven to be a technology that can benefit the dissemination of cultural content. In 2019 was the five hundredth anniversary of the death of Leonardo Da Vinci. Given the few works that develop IVR technologies to explain the genius of the master, we decided to take advantage of the opportunity to learn about the master through the use of new technologies. To build an IVR application that aims to spread knowledge, it is necessary to define an educational paradigm and the type of application. Given the domain of the application and the need to convey complex/novel topics, the IVR application developed in this study is based on the constructivist framework and creates a serious game (SG). In order to explain Leonardo Da Vinci's thinking and design approach, we decided to focus on urban planning and architecture studies by explaining the projects envisioned by Leonardo da Vinci. This paper investigates whether an IVR-SG application maintains the fundamental characteristics underlying disclosure processes, such as immersivity and a sense of presence. Two secondary school classes experienced this by evaluating the application through a psychometric questionnaire. The results show that immersivity and a sense of presence were evaluated positively.